2009
DOI: 10.1111/j.1476-5381.2008.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral rapamycin attenuates inflammation and enhances stability of atherosclerotic plaques in rabbits independent of serum lipid levels

Abstract: Background and purpose: Atherosclerotic plaque rupture and thrombosis are the main cause of acute coronary syndrome. The study was aimed to test the hypothesis that oral administration of rapamycin may attenuate inflammation, inhibit progression and enhance stability of atherosclerotic plaques. Experimental approach: Thirty New Zealand rabbits were subjected to balloon-induced endothelial injury of the abdominal aorta and were fed a diet of 1% cholesterol for 20 weeks. From week 9 to week 20, the animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…With increasing knowledge about therapies targeting atherosclerosis, many studies suggest that the induction of macrophage autophagy plays a protective role in plaque stabilization [34][35][36]. In addition, a growing body of data suggests that autophagy and apoptosis are activated under the same conditions, yet the crosstalk and interplay between them appear to be complex and controversial [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…With increasing knowledge about therapies targeting atherosclerosis, many studies suggest that the induction of macrophage autophagy plays a protective role in plaque stabilization [34][35][36]. In addition, a growing body of data suggests that autophagy and apoptosis are activated under the same conditions, yet the crosstalk and interplay between them appear to be complex and controversial [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that rapamycin supplementation reduces high-fat diet-induced atherosclerosis in apolipoprotein E-deficient (apoE − / − ) mice, 12 suppresses vascular inflammation, and enhances the stability of atherosclerotic plaques. 13 In addition, rapamycin might be involved in regulating phosphate homeostasis 14 and participate in osteoblastic differentiation. [15][16][17][18] Rapamycin is used as an immunosuppressive agent after kidney transplantation in specific cases, and mTOR signaling inhibition might be associated with renal function reserve in chronic kidney disease (CKD).…”
mentioning
confidence: 99%
“…In contrast, we recently demonstrated in the multicenter NOCTET trial (9) that conversion to everolimus and reduced CNI therapy in maintenance HTx patients does not appear to influence CAV progression as quantified by IVUS. Nevertheless, there are experimental and clinical data indicating that PSI agents can effectively attenuate inflammation and inhibit progression and promote stability of atherosclerotic plaques (10,11).…”
Section: Introductionmentioning
confidence: 99%